Object and Subject Approaches in the Psychology of Art Perception: A Review of Empirical Research - Leonova, A.V. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
The article presents an overview of modern research on the psychology of perception of fine art. Recently, this area has become increasingly in demand both at the theoretical and practical levels. In the theoretical aspect, this direction is important in connection with the increasing trends for the study of value orientations since appreciation of art and beauty are often considered among the highest human values. From a practical point of view, it is important because of the usage of works of fine art for therapeutic purposes, for example, in art therapy. As a result of the analysis of modern foreign research in the field of art perception, author of this article offers classification of works in this field, which includes two main approaches - object and subject. The object approach is close to the traditions established in cognitive psychology and examines patterns of human processing of aesthetic information related to the work of art itself. In the subjective approach, attention is focused on the viewer him/herself, those psychological features that make him aesthetically responsive. Additionally, a division is made between the study of aesthetic evaluations and judgments of viewers and their aesthetic experiences. In the final part of the article, the author suggests principles according to which object and subject models should be chosen for use in practical psychology. В статье представлен обзор исследований, посвященных психологии восприятия изобразительного искусства. Данное направление становится все более востребованным, как на теоретическом, так и на практическом уровнях. В теоретическом аспекте оно имеет значение в связи с усиливающимися тенденциями к изучению ценностных ориентиров, так как приобщение к искусству часто рассматривается среди высших в иерархии потребностей человека. С практической точки зрения психология восприятия искусства может иметь значение при использовании произведений изобразительного искусства в терапевтических целях, например в арт-терапии. В результате анализа современных зарубежных исследований в области психологии восприятия искусства автор данной статьи предлагает свою классификацию направления работ, включающую в себя два основных подхода - объектный и субъектный. Объектный подход близок к традициям, сложившимся в когнитивной психологии, и рассматривает закономерности обработки человеком получаемой эстетической информации, связанной с самим произведением искусства. В субъектном подходе внимание концентрируется на зрителе, тех его чертах и психологических особенностях, которые делают его эстетически отзывчивым. Отдельно в статье проводится разделение между изучением эстетических оценок зрителей и изучением их эстетических переживаний. В заключительной части статьи определяются принципы, согласно которым следует выбирать объектные и субъектные модели для применения в рамках практической психологии.